2016
DOI: 10.1111/arcm.12248
|View full text |Cite
|
Sign up to set email alerts
|

The Production, Distribution and Consumption of Metals and Alloys at Great Zimbabwe

Abstract: The legacy of vandalism and almost a century of continuous focus on drystone wall masonry is that little is known about metal craft production and consumption activities at Great Zimbabwe. Within these limitations, this paper attempts to explore the metallurgy of Great Zimbabwe, guided by the framework of archival, chronological and fieldwork‐ and laboratory‐based studies. The paper contends that residents of various components of Great Zimbabwe worked and processed their own metal, pointing to homestead‐level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
(60 reference statements)
0
33
1
Order By: Relevance
“…This conclusion was reached based on a correlation of the terminal date for Great Zimbabwe and the basal date for Khami (Sheppard and Swart 1967;Robinson 1961b;Huffman and Vogel 1991) and the perceived similarities between the material cultures of the two sites. However, recent research has demonstrated that Great Zimbabwe did not collapse in the fifteenth century, as was previously thought (Collett 1992;Bandama et al 2016). Instead it continued to flourish well into the sixteenth century, at a time when Khami was also developing in south-western Zimbabwe (Collett 1992).…”
Section: Khami Within the Zimbabwe Culturementioning
confidence: 85%
See 4 more Smart Citations
“…This conclusion was reached based on a correlation of the terminal date for Great Zimbabwe and the basal date for Khami (Sheppard and Swart 1967;Robinson 1961b;Huffman and Vogel 1991) and the perceived similarities between the material cultures of the two sites. However, recent research has demonstrated that Great Zimbabwe did not collapse in the fifteenth century, as was previously thought (Collett 1992;Bandama et al 2016). Instead it continued to flourish well into the sixteenth century, at a time when Khami was also developing in south-western Zimbabwe (Collett 1992).…”
Section: Khami Within the Zimbabwe Culturementioning
confidence: 85%
“…Studies of craft production have gained momentum over the years due to their importance in the broader study of material culture, economic organisation, socio-political organisation and exchange (Costin 2001;Hagstrum 2001;Bandama et al 2016). Costin (2005Costin ( : 1032 considers craft production as 'any transformational process involving skill, aesthetics and cultural meaning and consider the results of that crafting to be crafts'.…”
Section: Understanding Craft Productionmentioning
confidence: 99%
See 3 more Smart Citations